Electrochemical Properties and Ex Situ Study of Sodium Intercalation Cathode P2/P3-NaNi1/3Mn1/3Co1/3O2 - Minh Le Nguyen; Hoang Van Nguyen; Man Van Tran; Phung My Loan Le (Journal of Chemistry)
In recent work, P2/P3-NaNi1/3Mn1/3Co1/3O2 (NaNMC) was obtained by the sol-gel process followed by calcination of the precursor at 900°C for 12 h. The electrochemical properties of NaNMC were investigated in the voltage range of 2.0–4.0 V. The material exhibited an initial discharge capacity of 107 mAh·g−1 and good capacity retention of 82.2% after 100 cycles. Ex situ XRD performance showed that the P3-phase transformed from the P3- to O1-phase and vice versa, while the P2-phase remained stable during the sodium intercalation. The kinetic of sodium intercalation of NaNMC upon reversible Na+ insertion/deinsertion was evaluated via a Galvanostatic Intermittence Titration Technique (GITT) and Electrochemical impedance spectroscopy (EIS). The diffusion coefficients of Na+ ion deduced from the GITT curve have a broad distribution ranging from 10−10 to 10−11 cm2·s−1 for the charging/discharging process. Besides, the evolution of diffusion coefficient and charge transfer resistance is consistent with the complex phase transition generally observed in sodium layered oxides.